Flavonoids in the Prevention and Management of Oral Squamous Cell Carcinoma - Liza Meutia Sari; Dina Keumala Sari; Suzana Makpol (Cakradonya Dental Journal, 2026)
Oral squamous cell carcinoma (OSCC) accounts for the majority of occurrences of oral cancer, which is a common problem worldwide. Although standard treatments such as chemotherapy, radiation, and surgery available may have adverse side effects. A promising substitute for available modality therapies is molecular gene therapy, which targets genetic alterations connected to oral cancer. The purpose of this review is to explore the potential therapeutic benefits of flavonoids in OSCC prevention and treatment, based on epidemiological studies, in vitro and in vivo studies, and clinical trials. In this study, we reviewed 46 journals related to the efficacy of flavonoids in synthetic form or in plant herbs grouped them by 8 types of flavonoids, 8 countries that conducted flavonoid and oral cancer research, and 4 types of oral cancer inducer used. Our results showed the potential of natural flavonoids in molecular genetic disturbance and demonstrated their effect on oral cancer cells by causing apoptosis, cell cycle arrest, and inhibiting proliferation. The strategy of using flavonoids as therapy has the potential to lower death risks for oral squamous cell carcinoma and open the door to novel adjuvant medicines.